The Effectiveness of Using Interactive Chat Bots via Telegram in Developing Programming Skills in Python language among Middle School Students (The International Journal of Educational Sciences and Arts, 2024)
The study aimed to identify the effect of using chatbot in Telegram on developing Python programming skills for 7th graders in Jeddah. A quasi-experimental method was used by selecting a sample of (25) students as an experimental group. The study tools were pre and posttest for students’ knowledge of Python programming skills, and a rubric to observe students’ skills when practicing programming by Python. The study revealed that there were statistically significant differences at level (a£0.05) between the mean scores of experimental group in the pre and post-test. Also, there were statistically significant differences at the level (a£0.05) between the mean scores of experimental group in the observation rubric used to measure the students proficiency in using Python. Finally, this study had several recommendations and suggestions to use the interactive chatbot in programming skills and other education purposes.
Keywords: Programming Skills; Python Programming Language; Interactive Chatbot